Chondrocyte Aging: The Molecular Determinants and Therapeutic Opportunities - Ramasamy, Thamil Selvee; Yee, Yong Mei; Khan, Ilyas M. (Frontiers in Cell and Developmental Biology, 2021)
Osteoarthritis (OA) is a joint degenerative disease that is an exceedingly common problem associated with aging. Aging is the principal risk factor for OA, but damage–related physiopathology of articular chondrocytes probably drives the mechanisms of joint degeneration by a progressive decline in the homeostatic and regenerative capacity of cells. Cellular aging is the manifestation of a complex interplay of cellular and molecular pathways underpinned by transcriptional, translational and epigenetic mechanisms and niche factors, and unravelling this complexity will improve our understanding of underlying molecular changes that affect the ability of the articular cartilage to maintain or regenerate itself. This insight is imperative for developing new cell and drug therapies for OA disease that will target the specific causes of age-related functional decline. This review explores the key age-related changes within articular chondrocytes and discusses the molecular mechanisms that are commonly perturbed as cartilage ages and degenerates. Current efforts and emerging potential therapies in treating OA that are being employed to halt or decelerate the aging processes are also discussed.